1983
DOI: 10.1037/0021-843x.92.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Memory, emotion, and REM sleep.

Abstract: This article explores the manner in which REM sleep deprivation might affect various aspects of memory processing. A series of tests, including Sternberg's test of scanning of immediate memory, past personal and nonpersonal memory, and past emotional memories, was administered to eight subjects after baseline, control-awakening, and REM-deprivation nights. The results showed that only past, emotionally important memories may have been affected by REM deprivation; access to the emotion connected with the memori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The impairment of mood associated with this REM-related process might indicate that the attenuation of emotional tone by REM sleep is not functional in these patients. Similarly, in traumatized patients, increased nightmare frequency would point to a 1278,1294), in particular when containing high amounts of REM sleep (179,478,479,1274). The enhancing effect of postencoding sleep on emotional memories was detectable even after several years (1276).…”
Section: Sleep and The Erasure Of Information: Accounts Of Emotionmentioning
confidence: 92%
See 1 more Smart Citation
“…The impairment of mood associated with this REM-related process might indicate that the attenuation of emotional tone by REM sleep is not functional in these patients. Similarly, in traumatized patients, increased nightmare frequency would point to a 1278,1294), in particular when containing high amounts of REM sleep (179,478,479,1274). The enhancing effect of postencoding sleep on emotional memories was detectable even after several years (1276).…”
Section: Sleep and The Erasure Of Information: Accounts Of Emotionmentioning
confidence: 92%
“…In this regard, electrophysiological, neurochemical, and genetic conditions are considered that will be discussed in detail in the next sections. In fact, at a purely behavioral level, numerous studies have demonstrated that sleep after learning benefits declarative (17,18,60,63,79,290,326,327,343,348,350,376,408,427,431,478,479,547,560,571,574,592,603,682,732,735,861,898,930,932,959,1069,1172,1192,1217,1274,1276,1278,1282,1302) as well as nondeclarative kinds of procedural memory (135,147,164,311,322,374,383,435,447,563,…”
Section: F the Active System Consolidation Hypothesismentioning
confidence: 99%
“…This is likely to exacerbate their ADD‐related cognitive deficits and further impair their functioning. A wealth of research has shown deleterious effects of sleep deprivation on cognitive functioning even in non‐ADD subjects 28–31…”
Section: Difficulties In Awakeningmentioning
confidence: 99%
“…A wealth of research has shown deleterious effects of sleep deprivation on cognitive functioning even in non-ADD subjects. [28][29][30][31] Difficulty with morning awakening is not limited to persons who stay up excessively late due to insomnia or behavioral patterns inconsistent with sleep. A fair number of individuals with ADD report that they have chronic difficulty in awakening, even when they have had adequate sleep the night before.…”
Section: Difficulties In Awakeningmentioning
confidence: 99%
“…We also have found a disconnection from past meaningful memories in subjects who have been REM deprived (Greenberg et al 1983). A brief anecdote may speak most clearly to the kind of memory that is affected.…”
Section: [Hobson Et Al Nielsen Revonsuo Solms Vertes and Eastman]mentioning
confidence: 54%